G6PD Status in Patients with Presenile and Senile Cataract - Yasmin, Farzana; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2011)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the common enzymopathy and may be one of the risk factor for both presenile and senile cataract. Objective: To observe erythrocyte G6PD level in male patients with presenile and senile cataract in order to find out their enzyme status. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag Dhaka between 1st July 2009 and 30th June 2010. 60 male patients with presenile and senile cataract were included in the study group (Group-B). They were selected from Out patient Department (OPD) of Ophthalmology of BSMMU in Dhaka City. For comparison age matched 60 apparently healthy male without cataract (Group A) were also studied. According to age both study & control group were again subdivided in to Group B1 & A1(presenile,aged 40-60 years) and Group B2 & A2(senile, aged >60 years). Erythrocyte G6PD level was measured by Spectrophotometric method. Data were analyzed by independent sample t test, ANOVA, Chi-square test as applicable. Results: Mean erythrocyte G6PD level was significantly lower (P<0.01) in the presenile and senile cataractous groups compared to their corresponding noncataractous subjects. However 26.7% cataractous patients in presenile and 6.7% in senile group were G6PD deficient. Conclusion: Erythrocyte G6PD deficiency may be present in both presenile and senile cataract but more marked in presenile cataract patients. Key words: G6PD; Cataract. DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8058 J Bangladesh Soc Physiol. 2011 June; 6(1): 1-4